The Relationship Between Narcissism and Self-Esteem Amongst Soccer Players in The West Bank-Palestine - Awad Qasem Bodair (My University, 2013)
This study aimed to identify the level of both narcissism and self-esteem amongst soccer players in the West Bank- Palestine , and the relationship between them. In addition, to determine the differences in narcissism and self-esteem according to the club degree, playing experience, and playing center variables. To achieve this, the study was conducted on a sample of 210 players from professional and first and second soccer clubs in the West Bank , for data collection (Emmons', 1984) scale of narcissism , and Rosenberg self-esteem scale were used. After collecting the means, percentages, Pearson correlation coefficient , One Way ANOVA, and Scheffe post-hoc were used , and the study indicated the following results: - The level of narcissism of soccer players in the West Bank was high, where the percentage of the response reached (74.00 %). - The level of self-esteem of soccer players in the West Bank was moderate, where the percentage response reached ( 62.10 % ) . -There was a positive correlation between narcissism and self-esteem amongst soccer players in the West Bank, where the value of the correlation coefficient was high (0.78). - There were no statistically significant differences in the level of narcissism amongst soccer players in the West Bank due to the club degree, and playing experience, variables. - There were no statistically significant differences in the level of self-esteem amongst soccer players in the West Bank due to the club degree, playing experience, and playing center variables. - There were a statistically significant differences in the level of narcissism amongst soccer players in the West Bank due to the playing center in favor of the attackers. Based on the results of the study, the researcher recommended the following recommendations: - The need to take advantage of coaches from the results of the current study in psychological preparations for the soccer players in the West Bank. - The need to increase the interest of coaches in the development of self-esteem of soccer players in the West Bank. Key words: narcissism, self-esteem , Soccer, Palestine.

هدفت هذه الدراسة التعرف إلى مستوى كل من النرجسية وتقدير الذات لدى لاعبي كرة القدم في الضفة الغربية، والعلاقة بينهما، إضافة الى الفروق فيهما تبعاً الى متغيرات درجة النادي، والخبرة في اللعب، ومركز اللعب، ولتحقيق ذلك أجريت الدراسة على عينة قوامها (210) لاعباً من أندية المحترفين والدرجتين الأولى والثانية لكرة القدم في الضفة الغربية، ولغاية جمع البيانات طبق عليها مقياسان الأول مقياس امونز(Emmons,1984) للنرجسية والذي اشتمل على (37) فقرة موزعة على أربعة مجالات هي: (القيادة والسلطة، الإعجاب بالنفس، التفوق والغرور، العصابية). والآخر مقياس روزنبيرغ لقياس تقدير الذات والذي اشتمل على (10) فقرات. وبعد جمع البيانات عولجت إحصائياً باستخدام برنامج الرزم الاحصائية (SPSS) وتوصلت الدراسة الى النتائج الآتية: - إن المستوى الكلي للنرجسية لدى لاعبي كرة القدم في الضفة الغربية كان عالياً، حيث وصلت النسبة المئوية للاستجابة الى (74.00%). - أن المستوى الكلي لتقدير الذات، كان متوسطاً، حيث وصلت النسبة المئوية للاستجابة الى (62.10%). - وجود علاقة ارتباطية ايجابية دالة إحصائياً عند مستوى الدلالة (a=0.05) بين النرجسية وتقدير الذات لدى لاعبي كرة القدم في الضفة الغربية، حيث كانت قيمة معامل الارتباط عالية ووصلت إلى (0.78). - لا توجد فروق ذات دلالة إحصائية عند مستوى الدلالة (a=0.05) في مستوى النرجسية لدى لاعبي كرة القدم في الضفة الغربية تعزى إلى متغيري درجة النادي والخبرة في اللعب. - لا توجد فروق ذات دلالة إحصائية عند مستوى الدلالة (a=0.05) في مستوى تقدير الذات لدى لاعبي كرة القدم في الضفة الغربية تعزى إلى متغيرات درجة النادي، والخبرة في اللعب، ومركز اللعب. - توجد فروق ذات دلالة إحصائية عند مستوى الدلالة (a=0.05) في مستوى النرجسية لدى لاعبي كرة القدم في الضفة الغربية تعزى الى متغير مركز اللعب ولصالح المهاجمين. وبناءً على نتائج الدراسة أوصى الباحث بعدة توصيات من أهمها: - ضرورة استفادة المدربين من نتائج الدراسة الحالية في الإعداد النفسي للاعبي كرة القدم في الضفة الغربية. - ضرورة زيادة اهتمام المدربين في تنمية تقدير الذات لدى لاعبي كرة القدم في الضفة الغربية. الكلمات الدالة: النرجسية، تقدير الذات، كرة القدم، فلسطين.
العلاقة بين النّرجسية وتقدير الذات لدى لاعبي كرة القدم في الضفة الغربية-فلسطين